2016
DOI: 10.1111/jmft.12172
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Engagement Promotion in a Professionally Facilitated Online Intervention for Couples Affected by Breast Cancer

Abstract: Professionally facilitated web-based interventions for couples affected by an illness such as cancer are growing in popularity. Attrition rates for such online programs, however, are substantially higher than what is observed in face-to-face therapeutic contexts, and lower levels of participant engagement are associated with poorer outcomes. In the present investigation, a task analysis was employed to develop a model of engagement promotion in an online intervention for couples affected by breast cancer calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Some participants indicated that their meaningful experiences of providing systemic teletherapy were similar to conducting therapy face to face. One of Val's most meaningful experiences was “seeing couples benefit from the skills and tools they learn, watching them come closer together and learning how to love each other well, and seeing them have progressed towards their goals.” This aligns with previous telehealth research (Ianakieva et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Some participants indicated that their meaningful experiences of providing systemic teletherapy were similar to conducting therapy face to face. One of Val's most meaningful experiences was “seeing couples benefit from the skills and tools they learn, watching them come closer together and learning how to love each other well, and seeing them have progressed towards their goals.” This aligns with previous telehealth research (Ianakieva et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…One of Val's most meaningful experiences was "seeing couples benefit from the skills and tools they learn, watching them come closer together and learning how to love each other well, and seeing them have progressed towards their goals." This aligns with previous telehealth research (Ianakieva et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations